Strategi Pengembangan Agribisnis Porang Untuk Meningkatkan Kesejahteraan Petani - Andi Iva Mundiyah; Rahmawati Tahir; Andi Werawe Angka (JURNAL GALUNG TROPIKA, 2021)
Development in agriculture will be more optimal if it is combined with superior commodity management. One commodity that has the potential to become a leading commodity is the porang plant. The purpose of this study is to analyze internal and external factors in porang cultivation activities so that they can produce strategies to improve the welfare of porang farmers in the North Lombok Regency. Methods of data collection by observation and direct interviews. The analysis used is a SWOT analysis. The results of this study obtained strategies that can be used for the development of porang agribusiness in North Lombok Regency, namely: 1) Increasing business scale, 2) Increasing the quality of human resources, 3) Partnership patterns, 4) Use of quality packaging, 5) Timing of planting, 6) People's business credit, 7) Maximize the use of existing facilities and infrastructure. Overall efforts to improve farmers' welfare in porang agribusiness are to increase business scale with government support through small business loans for farmers and build partnerships with porang tuber processing industries.